2020
DOI: 10.21292/2075-1230-2020-98-8-46-56
|View full text |Cite
|
Sign up to set email alerts
|

The multicenter observational non-interventional study of combination anti-tuberculosis drugs used in treatment of pulmonary tuberculosis patients

Abstract: The objective of the study: to run a multicenter non-interventional observational study to assess treatment outcomes in tuberculosis patients receiving combination drugs with fixed doses, and to evaluate tolerability and safety of these drugs.Subjects and methods. 13 TB units participated in this study which lasted from 2016 to 2018. The primary population (PP) included of 489 patients, after applying the exclusion criteria – the subpopulation (subPP) included 267 patients with newly detected pulmonary tubercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…The destruction of MBT occurs faster, and the likelihood of drug resistance formation decreases (Faust et al 2019). A recent Russian multicenter observational study demonstrated that the use of fixed-dose combined anti-TB drugs in patients with newly diagnosed tuberculosis or its recurrence with preserved MBT sensitivity to Isoniazid and Rifampicin in chemotherapy regimens I and III was effective and was characterized by sufficient safety and tolerability (Tyulkova et al 2020).…”
Section: Stages and Regimens To Treat Tuberculosismentioning
confidence: 99%
“…The destruction of MBT occurs faster, and the likelihood of drug resistance formation decreases (Faust et al 2019). A recent Russian multicenter observational study demonstrated that the use of fixed-dose combined anti-TB drugs in patients with newly diagnosed tuberculosis or its recurrence with preserved MBT sensitivity to Isoniazid and Rifampicin in chemotherapy regimens I and III was effective and was characterized by sufficient safety and tolerability (Tyulkova et al 2020).…”
Section: Stages and Regimens To Treat Tuberculosismentioning
confidence: 99%